The effects of spinosad insecticide to adults of Apis mellifera, Megachile rotundata and Nomia melanderi (Hymenoptera: Apidae) - Mayer, D. F.; Kovács, G.; Brett, B. L.; Bisabri, B. L. (International Journal of Horticultural Science, 2001)
The toxicity of spinosad to adult female bees tended to be least to the honey bee (Apis mellifera L.) (LD50 = 0.078 pg/bee), intermediate to the alkali bee (Nomia melanderi) (0.065 pg/bee), and greatest to the alfalfa leafcutter bee (Megachile rotundata (F.)) (0.058 pg/bee), both in topical drop tests and in tests involving spinosad residues on alfalfa (Medicago sativa) foliage. For the calculated LD50 pg/g, the honey bee (LD50 = 0.612 pg/g) was the most susceptible followed by the alkali bee (0.773 pg/g) and the leafcutter bee (1.908 pg/g). The honey bee oral LD50 was 0.063 pg/bee and the calculated LD50 0.492 pg/g. Adding an adjuvant to spinosad sprays did not change the toxicity of spinosad to bees in residue bioassay studies. Spinosad at as high as 500 ppm in feeders containing a sucrose/honey syrup caused no significant reduction in honey bee visitation or total syrup consumed.